The Relevance of Lex Sportiva With Criminal Law on Football Sports Issues - Aufa Dhiya Ulhaq; Krish Rugchatjaroen (Faculty of Law Universitas Negeri Surabaya, 2024)
Football is the most popular sport and is in great demand by various groups of people. Its popularity is supported by accessibility, simplicity, major tournaments, social media and star players. In managing football internationally, FIFA was founded in 1904 as the world football governing body responsible for major matches such as the World Cup. FIFA functions as an organization that regulates football sovereignty through the principle of Lex Sportiva. In Indonesia, Lex Sportiva is recognized in Law No. 3 of 2005 which regulates the independent settlement of sports disputes. However, there are cases of violence in football that are resolved by criminal law. An example of a case that has occurred is Nanne Malomo in 2021 which sparked debate about the position of Lex Sportiva. In other countries, such as China, cases of football violations are often resolved without the intervention of criminal law. This can be exemplified by Oscar's punishment in the Chinese Super League. The objectives of this study are to: (1) determine the application of Lex Sportiva with Criminal Law to football sports problems; (2) determine the relationship between Lex Sportiva and criminal law to problems in football matches. This research method is conducted using a conceptual approach and a statute approach. The results of this study are (1) In national football competitions, the Lex Sportiva rules are based on the FIFA legal system, including the FIFA and PSSI Statutes. Criminal law in Indonesia uses the principles of Lex Specialis and Ultimum Remedium. Both principles are found in the Criminal Code and Law Number 3 of 2005 concerning the National Sports System; and (2) The relationship between lex sportiva and criminal law in Indonesia shows that although lex sportiva focuses on internal sports discipline, serious acts of violence on the football field often require criminal law intervention. Through dual application, both lex sportiva and criminal law work together to create justice and prevent future violence.